2020
DOI: 10.1136/vetreccr-2019-000966
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic‐assisted gastrotomy for foreign body retrieval in four dogs

Abstract: Four dogs with gastric foreign bodies were treated by laparoscopic-assisted gastrotomy. Techniques included two-port technique (n=two dogs), single-port with Alexis wound retractor (one) and single-port GelSeal cap with three cannulae (one). Foreign bodies retrieved included gravel (n=two dogs), trichobezoar (one) and a ball (one). All dogs had foreign bodies successfully removed, and no complications were encountered associated with the surgical procedures. These results suggest that laparoscopic-assisted gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The results described are consistent with those of other researchers. For example, E. Gibson et al (2020) indicated that the presence of feed masses or gases in the stomach makes ultrasound examination of the digestive tract less informative. Therewith, J.S.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results described are consistent with those of other researchers. For example, E. Gibson et al (2020) indicated that the presence of feed masses or gases in the stomach makes ultrasound examination of the digestive tract less informative. Therewith, J.S.…”
Section: Resultsmentioning
confidence: 99%
“…Otomo et al (2020), these parameters positively influenced the visibility of the pancreas and duodenum, likely related to the different body positions used for the study. E. Gibson et al (2020) expressed that a retrospective analysis of cases involving simultaneous abdominal US and endoscopy to assess the presence of anomalies in the stomach walls, foreign bodies, tumour localisation, and changes between the two examinations is more informative. Sonography and endoscopy are useful for diagnosing gastric neoplasia, with endoscopy being a more precise method for detecting gastric neoplasia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally, for targeted diagnosis of this group of diseases in veterinary practice, both general methods (palpation, auscultation) and instrumental methods (radiography, contrast radiography) of examination are used, according to D.A. According to E. Gibson et al (2020), special diagnostic methods for diseases of the digestive system include ultrasound examination, radiography, and endoscopy. E. Taillieu et al (2021) noted that, when necessary, the most informative method of investigation was chosen, or several types of additional instrumental studies were conducted, as they effectively complement each other.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results described are consistent with those of other researchers. For example, E. Gibson et al (2020) indicated that the presence of feed masses or gases in the stomach makes ultrasound examination of the digestive tract less informative. Therewith, J.S.…”
Section: Ukrainian Journal Of Veterinarymentioning
confidence: 99%